Pride and prejudice : extra-group paternity in lions and the effects of marker density on kinship and relatedness estimates - Jansson, Julia (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2017)
The development effective high-throughput sequencing techniques has allowed further insight to the mating systems of wild animal populations and challenged our perception that reproductive behaviour can be predicted from social structure. A recent study of lions (Panthera leo) in Etosha National Park, Namibia, found evidence of extra-group paternity (EGP) which has never before been confirmed among lions. Relatedness estimated from earlier research on lions in Selous Game Reserve, Tanzania, suggests that this population also deviates from a strict within-pride mating system. In this study, the same population of wild lions from Selous Game Reserve was visited two times, with twelve years in between, and with the aid of RAD-sequenced SNP markers, pedigrees were reconstructed and pairwise relatedness calculated to explore their mating system and compare with their social structure.